(untitled) (Palíndromo, 2020)
The article presents an artistic proposition that includes walking and drawing exercises, writing and body for the perception of a plant. The conception of nature is based on Goethe’s scientific studies and reflections on Craig Holdrege’s research. We seek to explore the possibilities of being open to the phenomena of nature, using the plant as a guide in the process.